EDF and the Brazilian power sector - Masvigner, Raphael Charlie Jean (2012)
Electricité de France (EDF) is a leading player in the European energy market by being both the first electricity producer in Europe and the world’s leading nuclear plant operator. EDF is also the first electricity producer and supplier in France. However, Europe, EDF’s core market, is currently underperforming: the European sovereign debt crisis is lowering significantly the growth perspective of an energy market that has already reached its maturity. As a consequence, European energy companies are now looking at international markets and especially BRIC economies where economic growth potential remains high. Among them, Brazil is expected to keep its strong economic and electricity demand growth perspectives for the coming decades. Though Brazil has not been considered as a strategic priority for EDF after the Light reversal in 2006, the current economic situation has led the Group to reconsider its position toward the country. EDF’s current presence in Brazil is limited to its stake in UTE Norte Fluminense, a thermal plant, located in the state of Rio de Janeiro. This report investigates the possibility and the feasibility of EDF’s activities expansion in Brazil and what added value it could bring for the Brazilian power market. Considering that the status quo would not allow EDF to take full advantage of Brazil’s future growth, this work is identifying the various options that are currently opened to EDF: market exit, status quo, EDF alone, local partner. For that purpose, this study collects and analyses the latest energy market data as well as generation companies’ information which are necessary to give a relevant overview of the current brazilian power sector and to present EDF strategic options for the country.